Sustainability of agroecological farms in Toacaso, Cotopaxi-Ecuador - Pacheco-Jiménez, Jacquelyn (2022)
The objective of this research was to determine the consequences of the adoption of agroecological production systems in the parish of Toacaso in terms of social, environmental, economic, and general sustainability. Considering the economic, social, cultural, and environmental dimensions, the methodology proposed by Sarandón (2002) was used to determine the indicators. The methodology proposed by Ortiz and Pradel (2009) was adopted in the evaluation of impacts in Integrated Pest Management programs. Surveys with questions related to the social, economic, and environmental consequences were conducted on 44 agroecological farmers and 44 conventional producers in the parish of Toacaso. Additionally, a sample of 44 conventional producers from the parish of Mulaló was identified as “control” treatment, which allowed to perform a comparison with and without the adoption of agroecological practices. The 27.27% of the 44 productive units that implemented the agroecological production system achieved general sustainability, the average general sustainability index was 2.16, where 86.36% achieved environmental sustainability, 47.72% economic sustainability, and 47.73% social sustainability.